The influence of audience and monetary reward on the putting kinematics of expert and novice golfers - Tanaka, Y.; Sekiya, H. (Research Quarterly for Exercise and Sport, 2010)
We investigated changes in movement kinematics and attentional focus when expert and novice golfers performed a golf-putting task under pressure. Six male professional golfers and five male novice golfers performed 100 acquisition trials, followed by 10 trials in the pressure condition with a performance-contingent cash reward and small audience. After the 10 trials in the pressure condition, participants answered a questionnaire concerning attentional focus during both types of trial, including such aspects as conscious control of movements and the effects of distraction. A pressure manipulation check revealed a modest increase in physiological arousal, in that heart rate increased by about 10 bpm although state anxiety did not increase. A two-dimensional analysis of movement kinematics revealed that the amplitudes of arm and club movements decreased on the backswing in the pressure condition. Arm and club movement speed decreased on the foreswing in both experts and novices. Furthermore, neither experts nor novices changed their attentional focus in the pressure condition. Whereas previous studies of "choking under pressure" focused on attentional changes, the kinematic changes found in the present study were possibly caused by the influences of strategy modification and/or emotional response. Choking phenomena can be explained by attentional changes, along with the influences of strategy modification and/or emotional response under pressure.